Given a unitary transformation $U_F(t)=\sum_n e^{in\omega t}\sum_{\lambda\in n}\left| \lambda, n\right\rangle \left\langle \lambda,n \right|$ applied to a Hamiltonian $H_0$ (with $H_0 \left|\lambda , n\right\rangle=\lambda\left|\lambda , n\right\rangle$, and where $(2n-1)\omega/2 < \lambda \leq (2n+1)\omega/2$ defines $n$), how does one obtain the "$(\lambda-n\omega)$" in the result $H_F=U_F(t)H_0U_F(t)^{-1}=\sum_n \sum_{\lambda \in n}(\lambda-n\omega)\left| \lambda, n\right\rangle \left\langle \lambda,n \right|$?


I'm trying to understand a "folding transform" as discussed by Maricq in his paper here, pages 5169-5170.

I'm leaving out extra bits of the Hamiltonian and other things, but the important features are these:


You have a Hamiltonian $H_0$, with eigenvalues $\lambda$. You're interested in how some value $\omega$ compares with the $\lambda$'s ($\omega$ is some driving frequency, say), so you break up your eigenvalues into regions indexed by $n$, with

$(2n-1)\omega/2 < \lambda \leq (2n+1)\omega/2$

and define your eigenvectors with this $n$ explicitly included: $H_0 \left|\lambda , n\right\rangle=\lambda\left|\lambda , n\right\rangle$. So, $n$ tells you what region your eigenvalue $\lambda$ is in.

Folding Transform

Now you define two operators: a projection operator $Q_n=\sum_{\lambda\in n}\left| \lambda, n\right\rangle \left\langle \lambda,n \right|$ and a transformation operator $U_F(t)=\sum_n e^{in\omega t}Q_n$.

The transformation operator $U_F(t)$ is applied to the Hamiltonian $H_0$ to produce a new "folded" Hamiltonian $H_F$ (presumably $H_F(t)=U_F(t)H_0U_F(t)^{-1}$, though this isn't made explicit), to produce the "folded" Hamiltonian:

$H_F(t)=\sum_n \sum_{\lambda \in n}(\lambda-n\omega)\left| \lambda, n\right\rangle \left\langle \lambda,n \right|$

Now the question: how did $(\lambda-n\omega)$ appear there? It seems to me it should just boil right back down to $\lambda$ again, not $(\lambda-n\omega)$.

  • $\begingroup$ U is a Sylvester clock matrix; work out its commutation relations with the original hamiltonian. The are not null. $\endgroup$ Apr 18, 2017 at 19:31
  • $\begingroup$ @CosmasZachos I thought it would simplify to $\lambda$ for a different reason, namely that $\sum_{n_1,\lambda \in n_1, n_2, \lambda \in n_2}e^{i(n_1-n_2) \omega t} \left| \lambda, n_1 \right\rangle \left\langle \lambda, n_1 \right| H_0 \left| \lambda, n_2 \right\rangle \left\langle \lambda, n_2 \right| = \sum_{n,\lambda \in n} \lambda \left| \lambda, n \right\rangle \left\langle \lambda, n \right| $ because of the matrix elements, not the exponential $\endgroup$
    – JDR
    Apr 18, 2017 at 20:39
  • $\begingroup$ I stand corrected. Their eqn (15) appears malformed, if one heeds the figure. One would expect the λs to now all be in the fundamental domain, n=1, or whatever. He appears to be transforming the propagators (3) with his operator, not the static hamiltonian you are writing here. $\endgroup$ Apr 18, 2017 at 22:22

1 Answer 1


Wow, I realized the answer while trying to answer to a different post.

The error was in assuming $H_F=U_F H_0 U_F^{-1}$. As we ALL know, this isn't how to go to a transformed frame! See here for a good local explanation of the rotating frame.

When you do things properly (transform your basis eigenvectors and deduce the evolution and effective Hamiltonian from there --- chain rule!) you get exactly the form above by differentiating $U_F$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.